Pengaruh Pendidikan Karakter terhadap Motivasi Belajar Siswa - Fithriyaani, Fathimah; Yudhyarta, Deddy Yusuf; Syarifudin, Syarifudin (Asatiza: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the effect of character education on students' learning motivation at State Elementary School 019 Sungai Beringin, Tembilahan Indragiri Hilir Riau Indonesia. This research used a quantitative approach. A total of 74 students were selected to participate in this study using the proportional random sampling technique. Data collection techniques were questionnaires and documentation. The data analysis technique used was a simple regression test. Based on the results of data analysis on variable X, namely Character Education, it was found that 73.69% was categorized as strong. Then, based on the results of data analysis of variable Y, namely Student Learning Motivation, it was found that 77.39% was also categorized as strong. While the effect of character education on student learning motivation obtained Fcount ≥ Ftable = 20.92 ≥ 3.97, so Ho is rejected, which means that there was a positive and significant influence between character education on student learning motivation